PREDIKSI FRAGMENTASI PELEDAKAN MENGGUNAKAN METODE KUZ-RAM DAN METODE IMAGE ANALYSIS DI BUKIT KARANG PUTIH PT. SEMEN PADANG - Rahma Febriani; Rusli HAR (Departemen Teknik Pertambangan FT UNP, 2023)
Limestone has massive and hard properties so that for production it is necessary to handle it by breaking up the rock mass. Separation of the rock mass is carried out by drilling and blasting which aims to split the rock according to the size of the rock fragmentation that has been planned. One of the factors for the success of a blasting operation is the size of the resulting rock fragmentation. where, later the size of the resulting fragmentation will affect the removal and disassembly of the blasted material. The company has a fragmentation target of no more than 15% with a size of ± 80 cm. The percentage of boulder from the actual results of blasting is ± 28%, thus disturbing the performance of the loading and unloading equipment to be ineffective and can result in production targets not being achieved. This research aims to determine the percentage size of fragmentation resulting from blasting activities theoretically and using Split Desktop Software. The results of this study are expected to be able to provide information to what extent the success of the blasting carried out by PT. Semen Padang, so that the company can determine the proper blasting geometry to use.The method used in analyzing the results of blasting fragmentation is using the Kuz Ram method and Spilt Desktop Software. The Kuz-Ram method pays close attention to the size of blasted rock fragmentation. In addition, analysis with the Kuz-Ram model is based on rock factor parameters, rock volume and explosives used. To find out the level of rock fragmentation resulting from blasting, you can use the Image Analysis Method, namely Split Desktop Software. Based on the data analysis performed, the percentage of fragmentation calculated using the split desktop software is 74.12% with a boulder percentage of 25.88%. Meanwhile, the prediction of fragmentation resulting from the Kuz-ram model is 71.98% with a boulder percentage of 28.02%